PENERAPAN HUKUM PERLINDUNGAN KONSUMEN TERHADAP KONSUMEN ECOMMERCE - Bisma Putra Pratama; Susanti Sembiring (Ensiklopedia of Journal, 2023)
E-commerce is a form of trade that has characteristics separate, namely trade that crosses national borders, does not meet them sellers and buyers, using the internet media. The birth of Information and Electronic Transactions (UU ITE) seems to be a solution to provide protection for consumers. The ITE Law regulates the legal requirements for an e-commerce transaction, regulates rights and obligations, prohibited actions, responsibility, legal protection, legal remedies and dispute resolution in e-commerce transactions. This Research Aims To Know about legal protection and legal remedies for consumers/buyers for losses caused by the Tokopedia Marketplace according to the law Consumer Protection Number 8 of 1999, the type of research the author uses in this research is normative juridical or library research namely examine the applicable legal provisions and the facts that occur in Consumer efforts to overcome losses due to the marketplace. Method Data collection was carried out by means of literature study and through review internet webKeywords: Protection, Consumer, E-Commerce